Senior Managers’ perception of their role in facilitating digital transformation in the public sector – South Africa - Mosia, Emanuel Mmuelli (University of the Witwatersrand, Johannesburg, 2024)
Digital transformation is a new phenomenon in the public sector. Previous studies have also found that public sector is performing poorly compared to private sector in their endeavours to transform. The study was intended to establish how senior managers perceive their role in facilitating digital transformation of the Department, excluding the actual assessment of digital maturity. The study drew guidance from Unified Model of Digital Maturity and Dynamic Capabilities Framework which both demonstrate the role of senior managers in the rapid changing environment due to technological disruptions. The study used semi- structured interviews to collect data from the population of 386 senior managers, where 15 senior managers were interviewed either face-to-face or virtually. The study finds that senior managers understanding of their role in facilitating digital transformation is fair to average. Their understanding of digital transformation is a simple switch from paper to paperless. Additionally, silo approach was found to be one of the impeders of digital transformation in the Department. The Department should be developing digital transformation strategy to guide the senior managers, coalesce all the efforts and be intentional in investing in digital transformation of the Department.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Digital transformation; Digitalisation; Public Sector; Senior Managers; Leadership; Innovation; UCTD; SDG-9: Industry, innovation and infrastructure